Sex differences in peripheral and central dysregulation of the kynurenine pathway in Parkinson’s disease - Leslie C. Jellen; Martha L. Escobar Galvis; Qiong Sha; Christine Isaguirre; Amy Johnson; Zach Madaj; Mechelle M. Lewis; Ryan D. Sheldon; Lan Kong; Xuemei Huang; Lena Brundin (npj Parkinson's Disease, 2025)
Abstract We previously demonstrated that kynurenine pathway (KP) dysregulation associates with Parkinson’s disease (PD) and its symptoms. Here, we profiled 16 KP-related markers in a second, independent cohort; plasma: n = 202 (116 PD (“OFF”), 86 controls); CSF: n = 183 (108, 75). Consistent with previous findings, we detected significantly higher concentrations of neurotoxic 3-hydroxykynurenine in plasma and lower concentrations of neuroprotective kynurenic acid along with higher neurotoxic quinolinic acid/kynurenic acid ratios in CSF of PD patients. Additionally, 10 markers showed sex-based differences, with more pronounced dysregulation in females. These 10 markers loaded to a single principal component linked to higher UPDRS I and II scores. Together, this suggests a composite signature of KP dysregulation in PD that is associated with worse symptoms and more prevalent in women. This work shows that KP dysregulation in peripheral and central compartments is linked to symptom severity in PD and warrants further systematic studies unraveling sex-dependent metabolic differences.